2017
DOI: 10.22547/ber/9.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Consumer Intentions to Adopt Online Banking in Malaysia

Abstract: As the world gradually shifts to the technological age, the number of digital savvy consumers has been growing exponentially. Such trends would eventually translate to increased consumer demand for digital related services such as online banking. Since online banking offers a number of benefits to the banking sector, therefore, banks need to deeply understand the factors which influence consumer intentions in adopting online banking. This paper investigates some of the most significant factors influencing cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 94 publications
1
9
0
Order By: Relevance
“…Support in the developing country context. Khan, Khan, and Xiang (2017) in the study of Factors Influencing Consumer Intentions to Adopt Online Banking in Malaysia found that mainly four constructs convenience, trust, perceived ease of use, and perceived usefulness significantly impact on consumer intention to use online banking. Different studies have shown that risk affects the attitudes negatively (Zhou, Lu, & Wang, 2010) and, therefore, intention to use technology (Herrero & San Martín, 2012;Herrero Crespo & Rodriguez del Bosque, 2010).…”
Section: Riskmentioning
confidence: 99%
“…Support in the developing country context. Khan, Khan, and Xiang (2017) in the study of Factors Influencing Consumer Intentions to Adopt Online Banking in Malaysia found that mainly four constructs convenience, trust, perceived ease of use, and perceived usefulness significantly impact on consumer intention to use online banking. Different studies have shown that risk affects the attitudes negatively (Zhou, Lu, & Wang, 2010) and, therefore, intention to use technology (Herrero & San Martín, 2012;Herrero Crespo & Rodriguez del Bosque, 2010).…”
Section: Riskmentioning
confidence: 99%
“…Such factors might affect the utilization of e-banking technique by the consumers. This study adds on to theoretically missing link identified by Khan et al (2017).…”
Section: Introductionmentioning
confidence: 76%
“…All of the results are justifying the gap identified by Khan et al (2017); Islamic Banks need to create awareness among their customers regarding use of e-banking for making the best use of services for the customers and resource saving for the banks themselves.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In a different context, Khan, et al (2017) studied the factors leading to customers' intention to use E-banking services in Malaysia. The study covered a sample of 200 respondents.…”
Section: Literature Review E-banking Acceptancementioning
confidence: 99%